The yeast endocytic protein Epsin 2 functions in a cell-division signaling pathway - Mukherjee, D. (2009)
The epsins are a family of adaptors involved in recruiting other endocytic proteins, binding of ubiquitylated cargo and induction of membrane curvature. These molecules bear a characteristic epsin N-terminal homology (ENTH) domain and multiple peptide motifs that mediate protein-protein interactions. We have previously demonstrated that the ENTH domain of epsin is involved in Cdc42 signaling regulation. Here, we present evidence that yeast epsin 2 (Ent2) plays a signaling role during cell division. We observed that overexpression of the ENTH domain of Ent2 (ENTH2), but not Ent1, promoted the formation of chains of cells and aberrant septa. This dominant-negative effect resulted from ENTH2-mediated interference with septin assembly pathways. We mapped the ENTH2 determinants responsible for induction of the phenotype and found them to be important for efficient binding to the septin regulatory protein, Bem3. Supporting a physiological role for epsin 2 in cell division, the protein localized to sites of polarized growth and cytokinesis and rescued a defect in cell division induced by Bem3 misregulation. Collectively, our findings provide a potential molecular mechanism linking endocytosis (via epsin 2) with signaling pathways regulating cell division.